Selective and electronic detection of COVID-19 (Coronavirus) using carbon nanotube field effect transistor-based biosensor: A proof-of concept study - Thanihaichelvan, M.; Surendran, S.N.; Kumanan, T.; Sutharsini, U.; Ravirajan, P.; Valluvan, R.; Tharsika, T. (University of Jaffna, 2021)
In this work, we propose and demonstrate a carbon nanotube (CNT) field-effect transistor (FET) based biosensor for selective detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). CNT FETs were fabricated on a flexible Kapton substrate and the sensor was fabricated by immobilizing the reverse sequence of the RNA-dependent RNA polymerase gene of SARS-CoV-2 onto the CNT channel. The biosensors were tested for the synthetic positive and control target sequences. The biosensor showed a selective sensing response to the positive target sequence with a limit of detection of 10 fM. The promising results from our study suggest that the CNT FET based biosensors can be used as a diagnostic tool for the detection of SARS-CoV-2. 2021 Elsevier Ltd. All rights reserved. Selection and peer-review under responsibility of the scientific committee of the Indo-UK International Virtual Conference on Advanced Nanomaterials for Energy and Environmental Applications (ICANEE 2020). This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/ licenses/by-nc-nd/4.0/).
Keywords: SARS-CoV-2; COVID-19; Biosensor; Rapid detection; Coronavirus; Carbon nanotube field-effect transistor